Internet of Things: Realising the Potential of a Trusted Smart World - Taylor,P; Allpress,S; Carr,M; Lupu,E; Norton,J; Smith,L; Blackstock,J; Boyes,H; Hudson-Smith,A; Brass,I; Chizari,H; Cooper,R; et al. (Royal Academy of Engineering: London, 2018)
This report examines the policy challenges for the Internet of Things (IoT), and raises a broad range of issues that need to be considered if policy is to be effective and the potential economic value of IoT is harnessed. It builds on the Blackett review, The Internet of Things: making the most of the second digital revolution, adding detailed knowledge based on research from the PETRAS Cybersecurity of the Internet of Things Research Hub and input from Fellows of the Royal Academy of Engineering. The report targets government policymakers, regulators, standards bodies and national funding bodies, and will also be of interest to suppliers and adopters of IoT products and services.